2020
DOI: 10.1002/mp.14535
|View full text |Cite
|
Sign up to set email alerts
|

The dose response of high‐resolution diode‐type detectors and the role of their structural components in strong magnetic field

Abstract: The dose response of high-resolution diode-type detectors and the role of their structural components in strong magnetic field

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 18 publications
(49 reference statements)
2
19
0
Order By: Relevance
“…Table 1: Diameters of the detectors including wall material and of the detectors sensitive area for all investigated point detectors as well as the sensitive detector volumes in mm 3 as calculated from finite-element methods taken from (Tekin et al, 2020) (*) or calculated using data given in (Tekin et al, 2022) The detector specific K(x) were derived according to Equation 1 from the measured D(x) and M(x) using the iterative van Cittert (1931) deconvolution method as described in Looe et al (2015). The number of iterations was limited to five to suppress the unavoidable noise amplification during the iteration process.…”
Section: Signal Profiles M(x)mentioning
confidence: 99%
“…Table 1: Diameters of the detectors including wall material and of the detectors sensitive area for all investigated point detectors as well as the sensitive detector volumes in mm 3 as calculated from finite-element methods taken from (Tekin et al, 2020) (*) or calculated using data given in (Tekin et al, 2022) The detector specific K(x) were derived according to Equation 1 from the measured D(x) and M(x) using the iterative van Cittert (1931) deconvolution method as described in Looe et al (2015). The number of iterations was limited to five to suppress the unavoidable noise amplification during the iteration process.…”
Section: Signal Profiles M(x)mentioning
confidence: 99%
“…For a perpendicular MRI-linac, the magnetic field correction factor includes a correction for the difference in dose deposition of 0.995 [8,9]. Tekin et al [26] has shown that the k B,Q for the microDiamond is approximately 1 when irradiated in "edge-on" orientation, i.e., the long axis of the microDiamond is aligned to the B 0 field direction and perpendicular to the radiation axis. The simulated correction factor for the microDiamond incorporates the correction for the difference in the dose deposition.…”
Section: Theorymentioning
confidence: 99%
“…Our work investigated the microDiamond as a crosscalibration detector for determination of ion chamber magnetic field correction factors via the ratio of the microDiamond and an ion chamber measured on both a conventional linac and a MRI-linac. The microDiamond was investigated due to the small energy dependence [25] and small magnetic field correction factor [26] associated with the detector.…”
Section: Introductionmentioning
confidence: 99%
“…Correction factors have been derived to account for this, and depends on the magnetic field strength and directions 26–31 . For solid state‐based detectors, there is no apparent changes within the bulk of the detection volume, rather the diode packaging and any air‐gaps surrounding the diodes generate changes in the secondary electron fluence 32–35 …”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29][30][31] For solid state-based detectors, there is no apparent changes within the bulk of the detection volume, rather the diode packaging and any air-gaps surrounding the diodes generate changes in the secondary electron fluence. [32][33][34][35] The purpose of the current work is to present the successful workings of a portable device capable of producing strong magnetic fields over a volume large enough to support fundamental small-scale experiments that mimic the environment of an MRI-linac system. The device is given the acronym MARDOS: Magnetic Apparatus for RaDiation Oncology Studies.…”
Section: Introductionmentioning
confidence: 99%